Synthesis Of Zincoxide Nanorods And Its Application To Humidity Sensor - Karki, Indra Bahadur; Nakarmi, Jeevan Jyoti; Chatterjee, Suman (Journal of Institute of Science and Technology, 2015)
The present study is concerned the sensing behavior of ZnO nanorods thin films application to humidity sensors. ZnO nanorods were fabricated on a glass substrate by sol-gel spin coating technique. The crystal structure of the resulting thin films was investigated by X-ray diffraction (XRD). Minimum crystalline grain size of this film was found about 5nm. Surface morphology of the film was investigated by Scanning Electron Microscope (SEM). SEM image shows rods like films which are evenly distributed on the surface of the sample. The film on a glass substrate explored for humidity sensing of controlled humid environment by measuring electrical resistance. The resistance falls from M Ohms to K ohms as percentage relative humidity increases from 20 to 90 %. Journal of Institute of Science and Technology, 2015, 20(1): 36-39